2019
DOI: 10.1093/eurheartj/ehz067
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficiency of a common and simplified protocol for pacemaker and defibrillator surveillance based on remote monitoring only: a long-term randomized trial (RM-ALONE)

Abstract: Aims This trial aimed to evaluate the safety and efficiency of a common and simplified protocol for the surveillance of cardiac implantable electronic devices based on remote monitoring (RM) in patients with pacemakers (PMs) and implantable cardiac defibrillators (ICDs) for at least 24 months. Methods and results The RM-ALONE is a multicentre prospective trial that randomly assigned 445 patients in two groups, both followed by RM: the home monitoring-only (HMo) based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 24 publications
3
56
2
1
Order By: Relevance
“…These results are consistent with the results of bivariate analysis that found no relevant differences in any outcome-including QALYs-or in costs (except for hospitalization), but contrast with those found in studies on costs and cost-effectiveness in other types of CIEDs (such as implantable cardioverter defibrillators or cardiac resynchronization therapies) in which there were significant differences-albeit not always relevant-found in utilization and costs favoring the telemonitoring group with equal or higher effectiveness [48][49][50][51][52][53][54][55][56], whereby suggesting that telemonitoring is a cost-effective (or dominant) alternative compared to conventional follow-up in hospital, as well as with the results of economic PM studies comparing both types of follow-up, suggesting lower utilization and costs, as well as cost-effective indices favoring remote monitoring alternatives [57].…”
Section: Discussionsupporting
confidence: 88%
“…These results are consistent with the results of bivariate analysis that found no relevant differences in any outcome-including QALYs-or in costs (except for hospitalization), but contrast with those found in studies on costs and cost-effectiveness in other types of CIEDs (such as implantable cardioverter defibrillators or cardiac resynchronization therapies) in which there were significant differences-albeit not always relevant-found in utilization and costs favoring the telemonitoring group with equal or higher effectiveness [48][49][50][51][52][53][54][55][56], whereby suggesting that telemonitoring is a cost-effective (or dominant) alternative compared to conventional follow-up in hospital, as well as with the results of economic PM studies comparing both types of follow-up, suggesting lower utilization and costs, as well as cost-effective indices favoring remote monitoring alternatives [57].…”
Section: Discussionsupporting
confidence: 88%
“…Another study in line with these findings is the RM-ALONE [4], a multicentre prospective trial assigned 445 patients to evaluate the efficiency and safety of RM in patients with PMs and implantable cardiac defibrillators (ICDs) during 24 months. The study reported that RM reduced 79.2% the number of face-to-face visits, decreasing the workload of the personnel.…”
Section: Discussionmentioning
confidence: 95%
“…The study reported that RM reduced 79.2% the number of face-to-face visits, decreasing the workload of the personnel. Continuous 'remote' contact with patients sending clinical reports avoided unnecessary visits, often resulting from patient anxiety [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations